The Intimate Governance of Land in Northern Uganda - Julaina Obika (Nordic Journal of African Studies, 2022)
After war in northern Uganda, conflicts over land became pervasive. Families, clans and neighbours often relate through tensions and contradictions over customary land and how it is governed. This article discusses the changing gendered dynamics of the governance of customary land amidst land conflicts in a post-war society. Drawing on fourteen months of ethnographic fieldwork in Pader District in the Acholi sub-region, carried out between 2014 and 2016, the paper highlights strategies that different categories of women involved in land conflicts use, to perform, communicate and activate their belonging and attachment to land. Relating the notion of property to how women (re)-position themselves in land conflicts, and (re)-construct those positions and their identities on and through land, demonstrates how these conflicts in post-war northern Ugandan offers women a way of grounding themselves on customary land. The article, therefore, advances the notion of ‘intimate governance’ to understand in particular, women’s increasing role in land governance, suggesting that it is becoming (en-)gendered through land conflicts.